1972
DOI: 10.1104/pp.50.1.176
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of a Glucan Containing Indole-3-acetic Acid

Abstract: The "bound auxin" of Zea mays, first described by Berger and Avery (Amer. J. Bot. 1944; 31: 199-203) has been purified and partially characterized. It is an indole-3-acetic acidcontaining, high molecular weight, lipophilic cellulosieglucan. The indole-3-acetic acid is in ester linkage as evidenced by indoleacetamide formation upon ammonolysis. The glucan is of variable chain length and comprises, in general, 35 to 50 per cent of the dry weight of the compound. The glucosidic residues are ,8 1 -e 4 linked and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…This was further confirmed for the pH 4.7 ester fraction by GLC. Similar results were obtained in the characterization of the high mol wt IAA ester fraction isolated from corn kernels (21). Thus, the carbohydrate portions of the oat IAA ester fractions, and of the high mol wt corn IAA ester fraction (2 1).…”
Section: Lsupporting
confidence: 71%
See 2 more Smart Citations
“…This was further confirmed for the pH 4.7 ester fraction by GLC. Similar results were obtained in the characterization of the high mol wt IAA ester fraction isolated from corn kernels (21). Thus, the carbohydrate portions of the oat IAA ester fractions, and of the high mol wt corn IAA ester fraction (2 1).…”
Section: Lsupporting
confidence: 71%
“…as yet. unidentified substances (21). The Avena IAA esters are, thus, analogous to the Zea A fraction, but differ in being water-soluble and precipitable from water by 50% or more acetone or alcohol.…”
Section: Lmentioning
confidence: 98%
See 1 more Smart Citation
“…Knowledge of pool size and rate of pool turnover has permitted: (a) identification of indole-3-acetyl-myo-inositol as the major chemical form for transport of indole-3-acetic acid (IAA) from endosperm to shoot; (b) demonstration that the free IAA of the endosperm is turning over rapidly with a half-life of 3.2 hours; (c) identification of esters of IAA as the immediate precursors of IAA in the endosperm and shoot-, (d) demonstration that neither tryptophan nor tryptamine is a major precursor of IAA for the seed or shoot-, (e) identification of IAA-myo-inositol glycosides as precursors of IAA-myo-inositol.It is concluded that seedlings of Zea mays utilize esters of IAA, and not tryptophan or its derivatives, for the IAA requirements of the germinating seedling.The endosperm of kernels of Zea mays contains small amounts of indole-3-acetic acid and large amounts of esterified IAA (5,15,26,27,35,38). The esterified IAA has been chemically characterized (1,21,26,36) and assayed quantitatively in the dry seed (35) and during ripening (9 and unpublished data) and during germination of the kernels (ref.…”
mentioning
confidence: 99%
“…The endosperm of kernels of Zea mays contains small amounts of indole-3-acetic acid and large amounts of esterified IAA (5,15,26,27,35,38). The esterified IAA has been chemically characterized (1,21,26,36) and assayed quantitatively in the dry seed (35) and during ripening (9 and unpublished data) and during germination of the kernels (ref.…”
mentioning
confidence: 99%